The history of the formation of Siberian black-and-white Holstein cattle (review) - K. S. Shatokhin; K. N. Narozhnykh; A. F. Petrov; M. A. Chechushkova; V. M. Norkinа; O. V. Efremova; E. V. Kamaldinov (Аграрная наука Евро-Северо-Востока, 2025)
The development of Siberian black-and-white Holstein cattle has been studied. The subject of the study was the history of the origin and domestication of the ancestral forms of Siberian black-and-white Holstein cattle, namely the Holstein, Soviet black-and-white breeds, indigenous cattle of Siberia and the western regions of Russia. It has been shown that cattle in western Russia most likely originated from wild auroch (Bos primigenius) that lived in North Africa or the Middle East. However, some records indicate the introduction of genes from the wild wisent (Bison bonasus). The Holstein breed originated from the European wild aurochs (Bos primigenius), but evolved without the influx of genes from Russian cattle. In turn, since the 18th century, Russian cattle have been periodically improved by producers of Frisian, Dutch, and then Holstein breeds. The origin of indigenous Siberian cattle is still a matter of debate. According to one hypothesis, the indigenous Siberian cattle are descendants of the wild aurochs (Bos primigenius), which was domesticated in North Africa and entered Siberia along with the migration of human tribes. Another theory attributes the indigenous Siberian cattle to the so-called TuranoMongolian group, the origin of which also raises questions. In the genome of modern representatives of Turano-Mongolian cattle, haplotypes peculiar to wild aurochs (Bos primigenius), zebu (Bos indicus), as well as markers not peculiar to any of these species were found. This may indicate the origin of Turano-Mongolian cattle from a separate wild ancestor, as well as the introduction of yak (Bos mutus) or another type of bull. Thus, the gene pool of Siberian black-and-white cattle is a unique genetic reserve that combines the adaptive qualities of local cattle and the high potential of dairy productivity inherited from the Holstein breed.